Análise do efeito de alterações de parâmetros de projeto em coletores solares planos para aquecimento de água - Silva, Gildásio de Paula (2016)
The objective of this work is to present the manufacturing parameters of the solar collectors, subject to modification, resulting in improved performance. A discretization of the components of the solar collector was made, identifying the points that could be improved, the importance of each one and its influence on the operation of the collector as a whole. These modifications were simulated by means of a mathematical model, namely: the position of the absorber surface; The distance between the absorber surface and transparent cover; The relationship between thickness and width of the absorber surface. The EES (Engineering Equation Solver) software was used to perform the simulation. The model that was implemented in the EES was a flat solar collector of 1.0 m². After the simulation was carried out, three prototypes were built, one with characteristics common to the collectors available in the market and called the Standard and two more manufactured with the proposed modifications. All the models were sent to the Thermal Efficiency test in a laboratory accredited by INMETRO. The results of the simulation indicated that the change in the position of the absorber surface shows an increase of 0.11 m² in the absorber area of the collector; The computational simulation indicated that the increase in the distance between the absorber surface and the transparent cover in the collectors generated an increase in heat loss from the top of the collector of 0.058 W / m²K; The change of the thickness and width of the absorber surface generated a reduction in the efficiency of 94% in the standard collector to 90% in the proposed prototype. The combination of the mounting position and the distance between the absorber surface and the cover showed a 5% increase in the energy production of this collector. For the results of the laboratory tests it was observed that the prototype with the modifications in the thickness and width of the absorber surface showed a decrease in its performance and the prototype with the combination of the mounting position with the distance between the absorber surface did not show an improvement in its performance , Which was contrary to the mathematical model and whose explanation is due to the uncertainty of ± 2.92% of the production line of the company supplying the prototypes.